Re-programing chromatin with a bifunctional LSD1/HDAC inhibitor induces therapeutic differentiation in DIPG - Anastas, JN; Zee, BM; Kalin, JH; Kim, M; Guo, R; Alexandrescu, S; Blanco, MA; Giera, S; Gillespie, SM; Das, J; Wu, M; Nocco, S; et al. (Cell Press, 2019)
H3K27M mutations resulting in epigenetic dysfunction are frequently observed in diffuse intrinsic pontine glioma (DIPGs), an incurable pediatric cancer. We conduct a CRISPR screen revealing that knockout of KDM1A encoding lysine-specific demethylase 1 (LSD1) sensitizes DIPG cells to histone deacetylase (HDAC) inhibitors. Consistently, Corin, a bifunctional inhibitor of HDACs and LSD1, potently inhibits DIPG growth in vitro and in xenografts. Mechanistically, Corin increases H3K27me3 levels suppressed by H3K27M histones, and simultaneously increases HDAC-targeted H3K27ac and LSD1-targeted H3K4me1 at differentiation-associated genes. Corin treatment induces cell death, cell-cycle arrest, and a cellular differentiation phenotype and drives transcriptional changes correlating with increased survival time in DIPG patients. These data suggest a strategy for treating DIPG by simultaneously inhibiting LSD1 and HDACs.